2001
DOI: 10.1292/jvms.63.167
|View full text |Cite
|
Sign up to set email alerts
|

Serum Growth Hormone and Insulin-Like Growth Factor-1 Concentrations in Japanese Black Cattle with Growth Retardation.

Abstract: ABSTRACT. Serum concentrations of growth hormone (GH) and insulin-like growth factor-1 (IGF-1) were determined in 5 calves in the same lineage with growth retardation. They had normal appetites, activities, body proportion, and laboratory test results. Calves with growth retardation had higher serum GH concentrations and lower serum IGF-1 concentrations. These findings suggested defects in the GH-IGF-1 axis, such as in the GH-receptor.KEY WORDS: growth hormone, growth-retarded cattle, insulin-like growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…Thus, strain-specific endocrine and metabolic features should be considered as well as their meat characteristics. Some researchers have considered growth retardation in Japanese black cattle to be intimately related to pedigree and to be hereditary [9,14,15]. Our data above might support their conclusions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, strain-specific endocrine and metabolic features should be considered as well as their meat characteristics. Some researchers have considered growth retardation in Japanese black cattle to be intimately related to pedigree and to be hereditary [9,14,15]. Our data above might support their conclusions.…”
Section: Discussionsupporting
confidence: 86%
“…However, more detailed knowledge of the causes for insufficient growth of cattle has yet to be obtained. Kitagawa et al [9] reported that cattle with growth retardation showed a high growth hormone (GH) concentration in spite of a low insulin-like growth factor-1 (IGF-1) concentration. Moreover, Oguro et al [15] concluded that the occurrence of ateliotic cattle is associated with the choice of a specific sire.…”
mentioning
confidence: 99%
“…72 (9): [1203][1204][1205][1206][1207][1208]2010 Considerable numbers of Japanese Black (JB) cattle suffer from retarded growth. The reasons for this are thought to be infectious diseases such as pneumonia, diarrhea and parasitic diseases [7,9]. However, many cattle with normal appetite and activities are also categorized as growth retarded [7-10, 13, 19-22, 24, 27].…”
mentioning
confidence: 99%
“…However, many cattle with normal appetite and activities are also categorized as growth retarded [7-10, 13, 19-22, 24, 27]. Kitagawa et al [8,9] and Takasu et al [19][20][21][22]24] investigated JB cattle with retarded growth and suggested that they had an abnormal IGF-1-GH axis that exhibits higher GH and lower IGF-1 concentrations. These retarded cattle also had abnormalities of energy and protein metabolism that were verified by their blood profiles.…”
mentioning
confidence: 99%
“…To reduce such losses, researchers have attempted to determine the cause of the growth retardation [5,6]. However, nutriture of the cattle with growth retardation has yet to be clarified.…”
mentioning
confidence: 99%